The role of anhedonia symptoms in symptomatology of posttraumatic stress disorder and related functional impairments among traumatized Chinese adults - Jiachen Wan; Ruojiao Fang; Ping Liu; Yajie Bi; Shu Luo; Chengqi Cao; Li Wang (European Journal of Psychotraumatology)
Background: Posttraumatic stress disorder (PTSD) is a mental disorder comprised of heterogeneous clinical symptoms. Various studies have demonstrated that anhedonia is a distinct symptom dimension of PTSD. However, the association between anhedonia dimension and different aspects of PTSD symptomatology remains unclear.Objective: This study examined the associations between anhedonia symptoms and PTSD diagnosis, overall symptom severity, and both psychosocial and physical functional impairments.Method: A total of 1,063 adult survivors of the 2008 Wenchuan earthquake were assessed nine years after the disaster. PTSD symptoms and functional outcomes were measured using the PTSD Checklist for DSM-5 (PCL-5) and the Short Form Health Survey (SF-36). Multiple regression analyses were conducted to examine the associations between anhedonia and key outcomes, controlling for relevant covariates. Partial correlation analyses were used to provide supplementary effect size estimates.Results: Anhedonia symptoms were significantly associated with both PTSD diagnosis and levels of overall symptoms, and specifically associated with psychosocial function impairments rather than physical function impairments. Relative to the other PTSD symptom dimensions anhedonia showed the second highest correlation with PTSD diagnosis and levels of overall symptoms and medium correlation with psychosocial function impairments.Conclusions: These findings suggest that anhedonia may represent an important symptom dimension within PTSD, particularly in relation to symptom severity and psychosocial functioning. The results highlight the potential value of further investigating anhedonia in both PTSD assessment and cross-diagnostic research.